DRIVING INNOVATIVE COMMUNITY ENGAGEMENT THROUGH KNOWLEDGE TRANSFER PROGRAMME - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PUTRAJAYA, 1 December 2015 – The Knowledge Transfer Programme (KTP) recognises a broad range of activities to support mutually beneficial collaboration between universities, industries and communities (government agencies/nongovernmental organisations/public sector).